The Role Of Pai Teachers In Increasing Prayer Interest In Smpn 1 Baturetno Wonogiri Students In 2023/2024 (The Role Of Pai Teachers Increases Interest In Prayer In Junior High School Students) - Hafid Zulhan Bachtiar; Zaenal Abidin (Jurnal Indonesia Sosial Teknologi, 2023)
The background of this research is the role of the PAI teacher in increasing prayer interest in students of SMP Negeri 1 Baturetno Wonogiri. This research method is qualitative, by interviewing teachers and conducting a survey using Google form at SMP Negeri 1 Baturetno. The results of the research are: teachers become supervisors, teachers become administrators, teachers become educators, and teachers become innovators. The inhibiting factors that are felt are: many students still don't immediately go to the mosque, students are found to go to the canteen, students who are still praying alone so they don't attend congregational prayers, places of worship that are less extensive so they cannot accommodate congregational prayers, there are other factors from the influencing parent. The solution to the inhibiting factors is: for the school to expand places of worship even though until now it has not been perfect, the teacher should inform the parents of students to carry out congregational prayers at home, as educators they must treat students fairly, interact with noble character, give advice and motivation.